2022
DOI: 10.3390/pathogens11070778
|View full text |Cite
|
Sign up to set email alerts
|

Visible 405 nm Violet-Blue Light Successfully Inactivates HIV-1 in Human Plasma

Abstract: Despite significant advances in ensuring the safety of the blood supply, there is continued risk of transfusion transmitted infections (TTIs) from newly emerging or re-emerging infections. Globally, several pathogen reduction technologies (PRTs) for blood safety have been in development as an alternative to traditional treatment methods. Despite broad spectrum antimicrobial efficacy, some of the approved ultraviolet (UV) light-based PRTs, understandably due to UV light-associated toxicities, fall short in pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The 405 nm light treatment of platelets was performed in a closed system (US Patent Application no. 62/236, 706, 2015) as previously reported (7,3,8). Briefly, the system contained a light source consisting of narrowband 405 nm LED arrays (FWHM ~20 nm; LED Engin, San Jose, CA, USA), with appropriate thermal management, and powered by LED drivers (Mean Well, Xinbei, Taiwan) and a shaker platform to have 60 rpm and 22 • C in order to provide the continuous agitation of the sample while maintaining consistent treatment conditions.…”
Section: The Delivery Of 405 Nm Violet-blue Lightmentioning
confidence: 57%
See 3 more Smart Citations
“…The 405 nm light treatment of platelets was performed in a closed system (US Patent Application no. 62/236, 706, 2015) as previously reported (7,3,8). Briefly, the system contained a light source consisting of narrowband 405 nm LED arrays (FWHM ~20 nm; LED Engin, San Jose, CA, USA), with appropriate thermal management, and powered by LED drivers (Mean Well, Xinbei, Taiwan) and a shaker platform to have 60 rpm and 22 • C in order to provide the continuous agitation of the sample while maintaining consistent treatment conditions.…”
Section: The Delivery Of 405 Nm Violet-blue Lightmentioning
confidence: 57%
“…These technologies require the addition of chelators, and sample exposure to UV light has been reported to reduce the in vitro quality of platelets [ 15 ], which calls for alternative methods that are gentler to the platelets. We have previously shown that 405 nm light is a potent pathogen inactivator for a number of bacteria, HIV-1, and the Trypanosoma cruzi parasite, while it is gentle on treated plasma and platelets in human plasma and on platelets stored for transfusion [ 3 , 4 , 5 , 6 , 7 , 8 ]. Platelets treated with 405 nm light behaved similar to the light-untreated platelets in terms of in vitro parameters such as pH, lactate release, activation/aggregation responses to collagen, and the in vivo response of survival and recovery in an immunodeficient SCID mouse model [ 3 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This preprint research paper has not been peer reviewed. Electronic copy available at: https://ssrn.com/abstract=4715023 P r e p r i n t n o t p e e r r e v i e w e d Human platelet concentrates treated with microbicidal 405 nm light retain hemostasis activity several bacteria, HIV-1, and parasites in plasma alone or in platelets suspended in plasma [8,9]. Further, we have shown that microbicidal 405 nm light does not affect the recovery and survival of the lighttreated platelets in a SCID mouse model [10], demonstrating the safety of the treatment for ex vivo platelets.…”
Section: Is Effective In Reducing (By Inactivation)mentioning
confidence: 99%